Dendritic Cells in Cancer Immunotherapy Clinical Trials: Are We Making Progress? - Butterfield, Lisa H. (Frontiers in Immunology, 2013)
Dendritic cells have been tested in cancer immunotherapy clinical trials for two decades. Over this time, the methods of dendritic cell culture (or manufacture) have evolved, the approaches for antigen loading have broadened, the maturation signals have varied and different sites of administration have been tested. The post-vaccination immunologic questions asked have also varied between trials and over time. In this review, we will consider multiple aspects of dendritic cell-based vaccines tested in cancer patients, including the cell culture, antigen loading, maturation and delivery, as well as what we have learned from testing immune responses in vaccinated patients who have benefitted clinically, and those who have not measurably benefitted.